PENERAPAN ANALISIS REGRESI LOGISTIK BINER PADA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA BERBELANJA ONLINE DI TIKTOK - Putji Alfayulanda; Dewi Murni (LPPM Universitas Bina Bangsa, 2024)
TikTok is a widely popular application among people of all age groups, from the young to the elderly. Students frequently utilize TikTok as a platform for online shopping, and there are numerous factors influencing their decisions. The research aims to construct a binary logistic regression equation model to determine the significant factors. The study population consists of all students from the Department of Mathematics who enrolled in 2022. The research sample comprises 71 respondents. The dependent variable (Y) in this study is the decision to shop on TikTok, and the independent variables (X) are trust (X1), service quality (X2), product diversity (X3), promotions (X4), security (X5), and price (X6). The research results indicate a binary logistic regression model as follows: π(x)=e^((13.012-1.679X_(2.1)-1.663X_(5.4)))/(1+e^((13.012-1.679X_(2.1)-1.663X_(5.4))) ) , where the service quality variable (X2) and security (X5) significantly influences the decision to shop online on TikTok